The Correlation Between Parents-Teachers Cooperation and Students’ Digital Literacy Development - Nasution, Liah Rosdiani (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
This correlational study investigates the parents' and teachers' cooperation regarding the students' digital literacy development in light of the transition to online learning. This study was conducted at SDN 200118 Padangsidimpuan, with 103 students recruited as a sample of this study. The data is collected from the questionnaires distributed to sample the class teachers and the students. The correlation between the two variables was analyzed with Pearson Product Moment Correlation in SPSS 23, in which the result shows the value of .565 and sig. 0.000 < 0.05. Thus, it can be stated that the alternative hypothesis, which states that there is a relationship between the parent and teacher cooperation variable with the development of students' digital literacy, is accepted.